Energy Poverty in the Polish Village – Experts’ Survey Report - Arkadiusz PIWOWAR (Communications of International Proceedings, 2020)
Poland faces serious challenges related to the provision of clean and affordable energy to its citizens, in addition, energy poverty is a significant problem, which most often affects the inhabitants of rural areas. In this paper, based on the analysis of primary data obtained through a survey of experts (agricultural advisors), the scope and causes of the phenomenon under study were identified. According to the research, almost half of the respondents assessed that energy poverty is a serious problem in rural areas in Poland. The research shows that the most important factor causing this problem is the cost of purchasing energy (the amount of energy price, distribution costs and taxes affecting the price). In experts' opinion, the problem of energy poverty is insufficiently emphasized in the media, in public and scientific discussions/debates.
Keywords: Energy Poverty; Rural Energy; Poland.